2018
DOI: 10.21873/invivo.11234
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Systemic Hyaluronan Synthesis Exacerbates Murine Hepatic Carcinogenesis

Abstract: Abstract. Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Some reports have shown that 4-MU inhibits the properties of CSCs by the inhibition of HA, accompanied by a reduction of CSC markers, like transmembrane glycoproteins CD44 and CD133, as well as CD90 and EpCAM cells, indicating a possible mechanism which involves HA in cell-to-cell and cell-to-matrix interactions (52,53). In contrast to these reports, Mikami et al showed that systemic inhibition of HA synthesis by oral 4-MU administration promotes the development of tumor in mice with liver tumors induced by administration of thioacetamide (TAA) (79). A possible explanation for this opposite result could be associated with the HCC model used by the authors.…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%
“…Some reports have shown that 4-MU inhibits the properties of CSCs by the inhibition of HA, accompanied by a reduction of CSC markers, like transmembrane glycoproteins CD44 and CD133, as well as CD90 and EpCAM cells, indicating a possible mechanism which involves HA in cell-to-cell and cell-to-matrix interactions (52,53). In contrast to these reports, Mikami et al showed that systemic inhibition of HA synthesis by oral 4-MU administration promotes the development of tumor in mice with liver tumors induced by administration of thioacetamide (TAA) (79). A possible explanation for this opposite result could be associated with the HCC model used by the authors.…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%
“…However, 4-MU treatment is not specific for any particular HAS, and can partially affect the synthesis of other GAG chains [102]. It is reported that 4-MU causes potential detrimental effects, as described for glycocalyx alteration in atherosclerotic animal models [109] and increased tumorigenicity in hepatocellular carcinoma mouse models [110]. Recently, the potential limited systemic efficacy of 4-methylumbelliferyl glucuronide (4-MUG) was tested in mice.…”
Section: Has Inhibition By 4-mumentioning
confidence: 99%
“…Long-term treatment with TAA alone has been demonstrated to induce HCC within 14-16 weeks in rats (69,70). Murine studies are much rarer in the literature and describe HCC development after 26 weeks to 12 months of TAA treatment (71)(72)(73)(74). Figure 2 illustrates tumor histology and characteristics of TAA-induced HCC development compared to CDE-mediated HCC development in mice after 7 months of treatment.…”
Section: Thioacetamide (Taa)mentioning
confidence: 99%